Identifikasi Fungsi dan Efektivitas Jalur Pejalan Kaki di Pusat Kota Banda Aceh - Atika Aditya; Yunita Arafah; Lestinesia Zahara; Nabilla Zuhra; Putri Talita Savira Dardaak; Kamiliya Aira Yasmin; Gaitsa Rizkina (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2024)
This study evaluates the function and effectiveness of pedestrian paths in the city center, focusing on their role in enhancing mobility, safety, and urban liveability. As cities shift towards sustainability, pedestrian paths are integral to improving walkability and accessibility. Using a mixed-methods approach, this research combines observation, questionnaires, and interviews to examine pedestrian path usage and user experiences in Banda Aceh’s city center business district. Observations revealed that the pedestrian path is used by pedestrians and shopkeepers, who display their goods on the walkway, thereby limiting pedestrian space and movement.